Analisis Efektivitas Penyuluhan Pencegahan Narkoba - Lovely Pricilia Sondakh; Atirah Suci Wulandari Ilhamyadi; Bunga Revana; Muh Ficqhi Taufik Ihsan; Nuraiman Nuraiman (Jurnal Informasi Pengabdian Masyarakat, 2026)
Drug abuse among adolescents is a serious problem that remains a challenge in the field of education, particularly at the junior high school level. Adolescence, characterized by a high level of curiosity and strong environmental influences, makes this group vulnerable to various forms of illicit substance abuse. This community service activity aims to analyze the effectiveness of drug prevention education at SMP Negeri 1 Palu in enhancing students’ knowledge and awareness of the dangers of drugs. The activity was implemented using a participatory educational approach with four main stages: preparation and coordination, conducting the education session, evaluating effectiveness through pre- and post-tests, and analyzing and reporting the results. The results of this activity indicate a significant increase in students’ knowledge levels following the education session. This is evidenced by improved student ability to understand the types of drugs, their effects, and the legal aspects governing drug abuse. Additionally, observations during the activity also showed increased active student participation in the learning process, reflecting heightened awareness and interest in the material presented. Thus, drug prevention outreach activities have proven effective in enhancing students’ understanding and awareness at SMP Negeri 1 Palu, and can serve as an important preventive strategy in efforts to prevent drug abuse within the school environment. These activities also underscore that an interactive educational approach plays a crucial role in fostering a preventive mindset among the younger generation regarding the dangers of drugs.